CDFA: Calibrated deep feature aggregation for screening synergistic drug combinations - Kang, Xiaorui; Liu, Xiaoyan; Zou, Quan; Li, Tiantian; Luo, Ximei (Frontiers in Pharmacology, 2025)
IntroductionDrug combination therapy represents a promising strategy for addressing complex diseases, offering the potential for improved efficacy while mitigating safety concerns. However, conventional wet-lab experimentation for identifying optimal drug combinations is resource-intensive due to the vast combinatorial search space. To address this challenge, computational methods leveraging machine learning and deep learning have emerged to effectively navigate this space.MethodsIn this study, we introduce a Calibrated Deep Feature Aggregation (CDFA) framework for screening synergistic drug combinations. Concretely, CDFA utilizes a novel cell line representation based on the protein information and gene expression capturing complementary biological determinants of drug response. Besides, a novel feature aggregation network is proposed based on the Transformer to model the intricate interactions between drug pairs and cell lines through multi-head attention mechanisms, enabling discovery of non-linear synergy patterns. Furthermore, a method is introduced to quantify and calibrate the uncertainties associated with CDFA’s predictions, enhancing the reliability of the identified synergistic drug combinations.ResultsExperiments results have demonstrated that CDFA outperforms existing state-of-the-art deep learning models.DiscussionThe superior performance of CDFA stems from its biologically informed cell line representation, its ability to capture complex non-linear drug-cell interactions via attention mechanisms, and its enhanced reliability through uncertainty calibration. This framework provides a robust computational tool for efficient and reliable drug combination screening.